A Novel Subunit Vaccine Based on Outer Capsid Proteins of Grass Carp Reovirus (GCRV) Provides Protective Immunity against GCRV Infection in Rare Minnow (Gobiocypris rarus) - Changyong Mu; Vikram N. Vakharia; Yong Zhou; Nan Jiang; Wenzhi Liu; Yan Meng; Yiqun Li; Mingyang Xue; Jieming Zhang; Lingbing Zeng; Qiwang Zhong; Yuding Fan (Pathogens, 2020)
The grass carp hemorrhagic disease, caused by the grass carp reovirus (GCRV), has resulted in severe economic losses in the aquaculture industry in China. VP4 and VP35 are outer capsid proteins of GCRV and can induce an immune response in the host. Here, three recombinant baculoviruses, AcMNPV-VP35, AcMNPV-VP4, and AcMNPV-VP35-VP4, were generated to express recombinant VP4 and VP35 proteins from GCRV type II in insect cells by using the Bac-to-Bac baculovirus expression system to create a novel subunit vaccine. The expression of recombinant VP35, VP4, and VP35-VP4 proteins in Sf-9 cells were confirmed by Western blotting and immunofluorescence. Recombinant VP35, VP4, and VP35-VP4 were purified from baculovirus-infected cell lysates and injected intraperitoneally (3 μg/fish) into the model rare minnow, Gobiocypris rarus. After 21 days, the immunized fish were challenged with virulent GCRV. Liver, spleen, and kidney samples were collected at different time intervals to evaluate the protective efficacy of the subunit vaccines. The mRNA expression levels of some immune-related genes detected by using quantitative real-time PCR (qRT-PCR) were significantly upregulated in the liver, spleen, and kidney, with higher expression levels in the VP35-VP4 group. The nonvaccinated fish group showed 100% mortality, whereas the VP35-VP4, VP4, and VP35 groups exhibited 67%, 60%, and 33% survival, respectively. In conclusion, our results revealed that recombinant VP35 and VP4 can induce immunity and protect against GCRV infection, with their combined use providing the best effect. Therefore, VP35 and VP4 proteins can be used as a novel subunit vaccine against GCRV infection.